ANALISA KONFLIK DUALISME KEPENGURUSAN KLUB SEPAK BOLA AREMA : (Berdasarkan Undang-Undang No: 28 Tahun 2004 Tentang Yayasan) - Hakam, Abdul; Haniyah, Haniyah; Ahmad Fandik, Rio; HANIYA (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2021)
The emerging football dualism inevitably triggered divisions in football in Indonesia. The consistency and loyalty of Indonesian fans, began to be divided with the emergence of two clubs with the same name but were in different competitions over this issue due to the Responsibility of the Foundation Management for the Transfer of Shares Based on Law No. 40 of 2007 concerning Arema Limited Liability Companies (PT) to the Public. The research method used is a normative research method with a statutory approach (Statute Aprouch) as a result of research, The conflict between the dualism of the Arema football club can be resolved by bringing together the two management of the Arema FC club which is in Liga 1 and Arema Indonesia which is in League 3 with the Arema Foundation as the owner of all Arema club assets. The coaching that is recognized is the name of the Coach which is in line with the updated data of the Ministry of Law and Human Rights